2019
DOI: 10.1080/21691401.2019.1687491
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and quantitative detection of urinary Cyfra21-1 using fluorescent nanosphere-based immunochromatographic test strip for diagnosis and prognostic monitoring of bladder cancer

Abstract: Bladder cancer is a common malignant tumour with high recurrence rate. Cytokeratin 19 fragments (Cyfra21-1) in urine has been regarded as a promising biomarker for the prognosis and diagnosis of bladder cancer due to the relevance of its high urinary level to the bladder cancer patients. However, currently detection methods of Cyfra21-1 have their limits, such as complicated steps, limited sensitivity or unsatisfying specificity. In this study, we developed a novel time-resolved fluoroimmuno test strip by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The preoperative serum Cyfra21-1 level was an independent predictor of lymph node metastasis in patients with esophageal squamous cancer (13). Rapid and quantitative detection of urinary Cyfra21-1 is a non-invasive approach for the diagnosis and prognosis of bladder cancer (14). In epithelial ovarian cancer, Cyfra21-1 was a poor prognostic factor associated with OS (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preoperative serum Cyfra21-1 level was an independent predictor of lymph node metastasis in patients with esophageal squamous cancer (13). Rapid and quantitative detection of urinary Cyfra21-1 is a non-invasive approach for the diagnosis and prognosis of bladder cancer (14). In epithelial ovarian cancer, Cyfra21-1 was a poor prognostic factor associated with OS (15).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been proven that Cyfra21-1 can independently be used as a prognostic indicator of a variety of malignant tumors. Numerous studies have shown that it has important prognostic significance for middle and advanced cancers, such as esophageal cancer, bladder cancer, epithelial ovarian cancer, and intrahepatic cholangiocarcinoma (13)(14)(15)(16). Lei et al found that Cyfra21-1 could be used to predict the early recurrence of OPSCC by comparing between groups, and the concentration of Cyfra21-1 was related to the clinicopathological stage of OPSCC.…”
Section: Introductionmentioning
confidence: 99%
“…In cancer cell imaging and theranostics, conventional bio-labeling with bio-reagents including organic dyes, chelates and fluorescent proteins has been used for some time now [11,12]. However, this type of labeling has disadvantages such as photobleaching, chemical and metabolic degradation, and a low signal-to-noise ratio, and therefore, in the case of neoplastic cancers, the use of high-sensitivity testing is severely impeded [13,14].…”
Section: Fluorescence Imaging and Nanoparticlesmentioning
confidence: 99%
“…Twelve studies investigated survivin, a protein which inhibits apoptosis allowing tumour cell survival (56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68). Fragments of cellular cytoskeletal proteins cytokeratins 8, 18, 19 and 20 (69) have also been found in urine of UBC patients, leading to the development of Urothelial Bladder Carcinoma-antigen assay (UBC) (66,(70)(71)(72)(73)(74)(75)(76)(77)(78)(79) and Cyfra21.1 (80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91). Vascular endothelial g r o w t h f a c t o r ( V E G F ) h a s b e e n i n v e s t i g a t e d i n 10 studies (59,64,86,(92)(93)(94)(95)(96)(97)(98).…”
Section: Proteinsmentioning
confidence: 99%